Statistical geoeffectiveness of solar-interplanetary disturbance events of type II radio bursts and CMEs/shocks - Yan, Jingye; Yu, Quanyingqi (Frontiers in Astronomy and Space Sciences, 2024)
Understanding and predicting the geoeffectiveness of solar activity on Earth is crucial for space weather. Therefore, predicting the impact of coronal mass ejections (CMEs) and their associated interplanetary (IP) shocks on Earth is essential. Observations of CMEs near the Sun can be used for these prediction and to study their propagation and evolution in IP space. Commonly used international models do not accurately predict whether and when IP shocks would reach Earth, thus failing to meet the demands of space weather forecasting. This study investigated the geoeffectiveness of solar-IP disturbance events, focusing on type II radio bursts from 1996 to 2019 (solar cycles 23 and 24). The study results showed that during this period, Wind/WAVES detected 623 type II bursts and 541 IP shocks at the L1 point, where 181 type II bursts were associated with L1 shocks. Approximately 29% of the IP shocks associated with type II bursts reached Earth, and approximately 34% of the IP shocks at the L1 point were accompanied by these bursts. IP type II radio bursts and their cutoff frequencies can serve as indicators of the geoeffectiveness of CMEs towards Earth. IP shocks accompanied by type II radio bursts cause stronger geomagnetic responses than those without the associated type II radio bursts. Lower cutoff frequencies of type II radio bursts increase the probability that the corresponding shocks reaching Earth, intensifying the geomagnetic response of the shock. Consequently, the presence of IP type II radio bursts and can serve as indicators of geoeffectiveness of the Earth-directed CMEs. Further, they help improve the accuracy of forecasting the geoeffectiveness of CME/shock events towards Earth.